g+-16g+-16g=-7

Simple and best practice solution for g+-16g+-16g=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for g+-16g+-16g=-7 equation:


Simplifying
g + -16g + -16g = -7

Combine like terms: g + -16g = -15g
-15g + -16g = -7

Combine like terms: -15g + -16g = -31g
-31g = -7

Solving
-31g = -7

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Divide each side by '-31'.
g = 0.2258064516

Simplifying
g = 0.2258064516

See similar equations:

| 3/63 | | 4.1x-19=26.1 | | 4p-4p=7 | | -4u-7=1 | | V(x)=(12-2x)(12-2x)(x) | | 3r-r+2=12 | | 6x-22=58+4x | | .03x=1391.82 | | 3=xt+3-5 | | x^4+(2m-1)x^2+m-3=0 | | x*.758=1055 | | -7v=-31 | | 15x+10-10x=2x+46 | | -3(m+16)+2=-4 | | -3a+a= | | -23=7w | | 4a-3a-1=13 | | x=-3+15+5 | | -23=-7w | | -24s=8 | | 19-2d=7 | | 3(N-12)=27 | | -10y+2+3y+8y=4 | | 6.4=-0.4x^2+10 | | 7(w+1)=9w+11 | | d/-2=2 | | -(y+5)+2y-11=-26 | | 4w+48=-2(w-9) | | -10.5-9.7=2w+1.4-1w | | 3(x+8)=63 | | 5p-4p+2p+3=12 | | 9^3X-1=1/27 |

Equations solver categories